Intra-Industry Trade sebagai Alternatif dalam Mengatasi Dampak Krisis Global di Indonesia - Yuliati, Lilis (Jurnal Trikonomika, 2012)
Issue of intra-industry trade (IIT) is increasingly discussed, since the concept was introduced by the Grubel-Lloyd in 1975. Empirically, the concept of IIT was developed in the 1980s in modern industrialized countries which coincidentally posses common endowment of factors, which tend to be capital intensive. The objectives of the study are threefold to obtain a figure of the intensity of IIT between Indonesia and ASEAN-4, to collect empirical evidence, examine and explain the factors that influence the intensity of IIT Indonesia with ASEAN-4. This study used Grubel-Lloyd Index and panel data analysis. The study showed the following results: Firstly IIT of Indonesianâ manufactures to ASEAN market-4 tend to experience a shift during the period 1985 to 2009 according to SITC categories The high commodity index in the initial year was declining over time in the subsequent years. Share intensity of IIT between Indonesia with four ASEAN member countries are included non IIT category because it was < 40%. Secondly, the intensity of IIT in manufactures based on ISIC category can be included in the category of IIT because it was â¥ 40%, namely 47.65%, while the remaining 52.35% is still belong to the non-IIT category. Thirdly, the estimation of the independent variables of the econometric model using FEM method, showed the following results: the intensity of labor and the economies of scale indicated no significant positive value. Market structure, product differentiation and dummy economic integration showed a significant positive value.